Ambivalent identity as abject in Maxine Hong Kingston’s The Woman Warrior and China Men - Yovela, Stasya; Priyatna, Aquarini; Prabasmoro, Tisna (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The Woman Warrior and China Men by Maxine Hong Kingston portray abject identity. Kingston’s Chinese American family in the novels seek to establish a superior identity over both the Americans, other Chinese people, and even their children who were born in America. This is apparent from the way the family views the white Americans and other Chinese people as ghosts and peasants respectively, hence displaying an ambivalence in regard to identity. By using the framework of feminist narratology and theories of abjection, mimicry, and identity, this article shows how identity as abject is realized through mimicry and displacement in the two novels. This article argues that Kingston’s Chinese American family disrespects while also reinforces the borders of identity. Because of their partial representation of identity, they are permanently displaced. Moreover, while they abject other identities to establish themselves, their own ambivalence makes them the abject that possesses a flexible identity.